Penerapan standar akuntansi keuangan usaha mikro, kecil, dan menengah berdasarkan SAK EMKM pada UMKM Dupa Desa Dalisodo Kabupaten Malang - Ekasari, Luh Dina; Handayanto, Adrian Junaidar; Sulistyowat, Yayuk (Jurnal Paradigma Ekonomika, 2021)
The purpose of the study was to examine the effect of accounting understanding on the quality of MSME financial statements. The data collection method used in this study was a questionnaire—determination of the number of samples using the Simple Random Sampling method. The analysis technique used is simple regression. The findings of the research show that the quality of MSME financial reports is influenced by accounting understanding. Adjusted R Square value of 0.742 means that 74.2% of the quality of financial statements is affected by accounting understanding Keywords: SAK EMKM, Understanding of Accounting, Quality of Financial Reports